Animal Nursing Assistant Textbook - Masters, Jo.; Martin, Carole, VN; British Veterinary Nursing Association (Edinburgh : Elsevier Butterworth-Heinemann, 2006)
A comprehensive guide for all students beginning their training as either animal nursing or animal care assistants, this text covers the entire syllabus of the course and provides a thorough grounding in the basics of veterinary nursing.
Includes index.
Published in association with BVNA.
Keywords: Veterinary nursing